An Efficient Biobjective Heuristic for Scheduling Workflows on Heterogeneous DVS-Enabled Processors - Pengji Zhou; Wei Zheng (Journal of Applied Mathematics)
Energy consumption has recently become a major concern to multiprocessor computing systems, of which the primary performance goal has traditionally been reducing execution time of applications. In the context of scheduling, there have been increasing research interests on algorithms using dynamic voltage scaling (DVS), which allows processors to operate at lower voltage supply levels at the expense of sacrificing processing speed, to acquire a satisfactory trade-off between quality of schedule and energy consumption. The problem considered in this paper is to find a schedule for a workflow, which is normally a precedence constrained application, on a bounded number of heterogeneous DVS-enabled processors, so as to minimize both makespan (overall execution time of the application) and energy consumption. A fast and efficient heuristic is proposed and evaluated using simulation with two real-world applications as well as randomly generated ones.